AN ANALYTICAL STUDY OF DIFFERENCE IN NON-PERFORMING ASSETS OF PUBLIC AND PRIVATE SECTOR BANKS (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Banking and financial sector gets utmost priority in the era of globalization. NPA has become a serious problem for Indian banking sector. The NPA figures of public sector banks are always in the debate as they dominate the banking industry and compared to private sector banks, they have much larger NPA. The present study focuses on the difference in NPA of public and private sector banks and factors responsible for the differences. Through Welch t-test it has been found that private sector banks are managing their NPA better than Public sector banks.